ON THE OCCURRENCE OF CHIMAEROID EGG CAPSULE OFF TUTICORIN, GULF OF MANNAR - Arumugam, G; Balasubramaniam, T S; Rajapackiam, S (Indian Journal of Fisheries, 2011)
The occurrence of two chimaeroid egg capsules off Tuticorin, Gulf of Mannar from commercial deep sea catch at a depth of 250 - 400 m during January 1990 is reported. A brief description of the morphometric characters of the egg cases is also given